MIGRANT HEALTH AND RESILIENCE - Koehn, Peter H. ([S.l.])
1 online resource.
Keywords: In an era of escalating conflict-induced and climate-induced migration and cross-border interaction, transnational-competence (TC) preparation for displaced persons, members of their host communities, humanitarian responders, and health-care professionals is increasingly critical. Building on insights from those engaged with a range of humanitarian crises and global-justice contexts, along with multidisciplinary research findings, this cutting-edge volume provides practical guidelines for preparing stakeholders for effective short-term and long-term responses to challenges arising in the wake of population dislocation generated by armed conflict, persecution, and climate change. Addressing the need to equip humanitarian care-givers and care-receivers with valuable skills for working together across barriers and boundaries, the guidance presented in the book enables educators, trainers, and field-based multinational and local responders to enhance and evaluate the quality and sustainability of humanitarian efforts that promote and bolster resilience and belonging and augment well-being, justice, and sustainable development. It features comprehensive TC-teaching and learning strategies coupled with tailored on-site and remote approaches and methods. Authoritative and insightful, Migrant Health and Resilience will be essential reading for the staff of NGOs, international organizations, national and local governments, and professional bodies working in development and humanitarian-crisis contexts, as well as for students, higher-education instructors, scholars, and evaluators.